Seamless steel pipe, method for piercing material to be rolled, and method for manufacturing seamless steel pipe

By optimizing drilling and rolling conditions with controlled circumferential shear strain, the method addresses the challenge of achieving high strength and toughness in seamless steel pipes, even at low surface reduction ratios, resulting in enhanced mechanical properties.

JP2025048722AActive Publication Date: 2025-04-03JFE STEEL CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024089863
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-21
Filing Date
2024-06-03
Publication Date
2025-04-03
Estimated Expiration
2044-06-03

AI Technical Summary

Technical Problem

Existing methods for manufacturing seamless steel pipes struggle to achieve sufficient processing strain to refine ferrite grains, especially when the surface reduction ratio is low, resulting in inadequate strength and toughness.

Method used

Optimizing the conditions for drilling and rolling by introducing appropriate circumferential shear strain into the material, which refines the ferrite grain size and enhances mechanical properties, even at low surface reduction ratios.

Benefits of technology

The approach results in seamless steel pipes with yield strengths of 758 MPa or more and toughness values of 60J or more at room temperature, while maintaining product sizes with low surface reduction rates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025048722000001_ABST
    Figure 2025048722000001_ABST
Patent Text Reader

Abstract

To provide a seamless steel pipe, a method for piercing a seamless steel pipe, and a method for manufacturing a seamless steel pipe, the seamless steel pipe having excellent strength and toughness.SOLUTION: Provided is a seamless steel pipe having a structure comprising: 40% or more of tempered martensite phase by volume; 25% or more and 40% or less of ferrite phase by volume; and more than 10% and 25% or less of retained austenite phase by volume. When crystal grains with a crystal orientation difference of 15° or less are regarded as the same crystal grain, the average ferrite grain size is 35 μm or less, the yield strength is 758 MPa or more, and the toughness value at 25°C is 60 J or more.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a seamless steel pipe, a method for drilling a rolled material, and a method for manufacturing a seamless steel pipe, and in particular to a technology for realizing high strength and high toughness of a seamless steel pipe by refinement of the crystal grains contained in the seamless steel pipe. [Background technology]

[0002] In view of the expected depletion of energy resources in the near future, development of deep oil fields and oil wells in severe corrosive environments, which have not been considered in the past, is being actively carried out. Seamless steel pipes used in such environments are required to have excellent mechanical properties and corrosion resistance.

[0003] In response to such requirements, Patent Document 1 describes, in mass %, C: 0.05% or less, Si: 1.0% or less, Mn: 0.1 to 0.5%, P: 0.05% or less, S: less than 0.005%, Cr: more than 15.0% and less than 19.0%, Mo: more than 2.0% and less than 2.8%, Cu: 0.3 to 3.5%, Ni: 3.0% or more and less than 5.0%, W: 0.1 to 3.0%, Nb: 0.07 to 0.5%, V: 0.01 to 0.5%, Al: 0.001 to 0.1%, N: 0.010 to 0.100%, O: 0.01% or less, B: 0.0005-0.0100%, with Nb, Ta, C, N and Cu satisfying specific formulas, having a structure consisting of 45% or more tempered martensite phase, 20-40% ferrite phase, and more than 10% but not more than 25% retained austenite phase, by volume fraction, and when crystal grains with a crystal orientation difference of 15° or less are defined as the same crystal grain, the maximum crystal grain size of the ferrite crystal grains is 500 μm or less, and a high-strength stainless steel seamless pipe for oil wells with excellent mechanical properties and corrosion resistance can be obtained.

[0004] Patent Document 2 also describes a high-strength stainless steel seamless pipe for oil wells which contains, by mass%, C: 0.002-0.05%, Si: 0.05-0.50%, Mn: 0.04-1.80%, P: 0.030% or less, S: 0.002% or less, Cr: more than 14.0% and 17.0% or less, Ni: 4.0-8.0%, Mo: 1.5-3.0%, Al: 0.005-0.10%, V: 0.005-0.20%, Co: 0.01-1.0%, N: 0.002-0.15%, and O: 0.006% or less, satisfies a specific formula, has a structure in which the average grain size of prior austenite is 40 μm or less, and has a yield strength of 1034 MPa or more. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2019 / 035329 [Patent Document 2] Patent No. 7201094 Summary of the Invention [Problem to be solved by the invention]

[0006] The technologies described in Patent Documents 1 and 2 can obtain excellent mechanical properties and corrosion resistance by optimizing the components, etc. However, for product sizes in which the area reduction rate shown in the following formula (1) cannot be increased, sufficient processing strain cannot be ensured to refine the crystal grains of the ferrite phase, and so the desired strength and toughness may not be obtained. Reduction rate (%) = 100 × (circumferential cross-sectional area of ​​round billet (mm 2 )-Circumferential cross-sectional area of ​​the blank pipe after piercing and rolling (mm 2 )) / Circumferential cross-sectional area of ​​round billet (mm 2 ) · · · (1)

[0007] The present invention has been developed in consideration of the above-mentioned problems, and aims to provide a seamless steel pipe having excellent strength and toughness, a method for piercing a rolled material to obtain the seamless steel pipe, and a method for manufacturing the seamless steel pipe. In the present invention, excellent strength refers to a yield strength of 758 MPa or more measured in accordance with the API 5CT standard, and excellent toughness refers to a toughness value of 60 J or more at room temperature (25°C) measured in accordance with the JIS Z 2242 (2023) standard. [Means for solving the problem]

[0008] As a result of the inventors' investigations, it was found that even when the area reduction rate is low, by optimizing the piercing and rolling conditions, it is possible to refine the ferrite grain size of a seamless steel pipe and obtain excellent mechanical properties. Specifically, the inventors have investigated methods for refining grain size in the manufacturing process of seamless steel pipes, and have found that even for product sizes where the area reduction rate cannot be increased, the grain size can be refined by introducing an appropriate circumferential shear strain into the rolled material. Therefore, the present inventors have investigated optimization of piercing-rolling conditions in order to refine the grains of a mother pipe. The present invention has been made based on the above findings, and the gist of the present invention is as follows.

[0009] [1] Volume ratio: 40% or more tempered martensite phase; 25% to 40% ferrite phase; A structure consisting of more than 10% and not more than 25% retained austenite phase, When crystal grains with a crystal orientation difference of 15° or less are defined as the same crystal grain, the average ferrite grain size is 35 μm or less, The yield strength is 758 MPa or more, A seamless steel pipe having a toughness value of 60J or more at 25℃. [2] The composition, by mass%, is: C: 0.002-0.05%, Si: 0.05 to 0.6%, Mn: 0.1-0.5%, Cu: 0.9-3.5%, Ni: 3.0-6.0%, Cr: 16.5-19%, Mo: 1-4%, N: 0.01-0.2%, Contains moreover, P: 0.02% or less, S: 0.002% or less, Al: 0-1%, V: 0~0.6%, Nb: 0-0.5%, W: 0-3.50%, Co: 0-1.5% The seamless steel pipe according to the above [1], wherein the balance consists of Fe and unavoidable impurities. [3] A method for piercing a rolled material when producing a seamless steel pipe according to the above [1] or [2], A method for piercing rolled material in which the circumferential shear strain imparted to the center of the thickness of the rolled material by piercing-rolling satisfies 0.48 or more. [4] A method for producing a seamless steel pipe, comprising the steps of: producing a seamless steel pipe using the method for drilling a rolled material described in [3] above. Effect of the Invention

[0010] According to the present invention, there are provided a seamless steel pipe having excellent strength and toughness, a method of piercing a rolled material for obtaining the seamless steel pipe, and a method of manufacturing the seamless steel pipe. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a diagram for explaining the positions at which samples for tissue observation were taken. [Diagram 2] FIG. 2 is a schematic diagram showing the steps of the Mannesmann mandrel mill process. [Diagram 3] FIG. 3 is a diagram for explaining the API5CT arched tensile test specimen and V-notch test specimen used in the evaluation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] [Seamless steel pipe] The present invention will be described in detail below. The seamless steel pipe of the present invention has a structure consisting of, by volume, 40% or more of tempered martensite phase, 25% to 40% of ferrite phase, and more than 10% to 25% of retained austenite phase, and when crystal grains with a crystal orientation difference of 15° or less are defined as the same crystal grain, the average ferrite grain size is 35 μm or less, the yield strength is 758 MPa or more, and the toughness value at 25°C is 60 J or more.

[0013] <Organization> Volume fraction of tempered martensite phase: 40% or more Volume fraction of ferrite phase: 25% to 40% Volume fraction of retained austenite phase: More than 10% and less than 25% In the seamless steel pipe of the present invention, in order to ensure a desired strength, the volume fraction of the tempered martensite phase is set to 40% or more, and preferably to less than 65%. The ferrite phase is precipitated at a volume fraction of 25% or more. This makes it possible to suppress the concentration of strain in the ferrite phase during hot rolling. On the other hand, if a large amount of ferrite phase is precipitated at a volume fraction of more than 40%, it may not be possible to ensure the desired strength. For this reason, the ferrite phase is precipitated at a volume fraction of 25% to 40%.

[0014] Furthermore, in the seamless steel pipe of the present invention, a retained austenite phase is precipitated in addition to the ferrite phase. The presence of the retained austenite phase improves ductility and toughness. In order to obtain such an effect of improving ductility and toughness while ensuring the desired strength, the retained austenite phase is precipitated so that its volume fraction exceeds 10%. On the other hand, precipitation of a large amount of austenite phase, which exceeds 25% by volume, makes it impossible to ensure the desired strength. For this reason, the retained austenite phase is set to a volume fraction of 25% or less. Preferably, the retained austenite phase is set to a volume fraction of more than 10% and not more than 20%.

[0015] FIG. 1 is a diagram for explaining the positions at which samples for tissue observation were taken. Here, in order to measure the above-mentioned structure of the seamless steel pipe of the present invention, first, a test piece for structure observation was taken from the center of the wall thickness (at t / 2 position (t: wall thickness)) of a cross section (circumferential cross section of the mother pipe) perpendicular to the pipe axis direction of the seamless steel pipe (see symbol X in Fig. 1). The taken sample (test piece for structure observation) was corroded with Villela's reagent (a mixture of picric acid, hydrochloric acid and ethanol in the proportions of 2 g, 10 ml and 100 ml, respectively), and the structure in the center of the wall thickness was photographed with a scanning electron microscope (magnification: 1000 times, field of view: 450 μm × 450 μm), and the structure fraction (volume %) of the ferrite phase was calculated using an image analyzer.

[0016] The test piece for X-ray diffraction is then ground and polished so that the cross section perpendicular to the tube axis direction (circumferential cross section of the bare tube) becomes the measurement surface, and the amount of retained austenite (γ) is measured using X-ray diffraction. The amount of retained austenite was calculated by measuring the integrated intensity of the diffracted X-rays on the (220) plane of γ and the (211) plane of α, using the following formula: γ(volume ratio)=100 / (1+(IαRγ / IγRα)) (where Iα is the integrated intensity of α, Rα is the theoretically calculated value of α, Iγ is the integrated intensity of γ, and Rγ is the theoretically calculated value of γ) The fraction (volume fraction) of the tempered martensite phase is the remainder other than the ferrite phase and the retained austenite phase determined by the above-mentioned measuring method.

[0017] Ferrite average grain size: 35μm or less The seamless steel pipe of the present invention is characterized in that the average ferrite grain size (hereinafter also referred to as the average ferrite grain size) is 35 μm or less when grains with a crystal orientation difference of 15° or less are defined as identical grains. If the average ferrite grain size exceeds 35 μm, the ferrite becomes coarse, and at least one of the strength and toughness deteriorates. Therefore, in the present invention, the average ferrite grain size is set to 35 μm or less. The average ferrite grain size (average ferrite grain size) is preferably 30 μm or less, and more preferably 27 μm or less. Although there is no particular lower limit, the average ferrite grain size (average ferrite crystal grain size) may be 20 μm or more, or may be 24 μm or more.

[0018] The measurement region of the average grain size of ferrite in the seamless steel pipe 10 is the central part of the wall thickness of the seamless steel pipe 10 (see symbol X in FIG. 1), as shown in FIG. The average grain size of ferrite was measured at 100 mm using electron backscatter diffraction (EBSD). 2 The crystal orientation is measured for a continuous region of the above, and grains with a crystal orientation difference of 15° or less are defined as the same crystal grain, and the average value of the ferrite crystals (number average value (= sum of grain size / number of crystal grains)) is calculated.

[0019] <Component composition> The chemical composition of the seamless steel pipe of the present invention is not particularly limited, but it is preferable that the seamless steel pipe contains, by mass%, C: 0.002-0.05%, Si: 0.05-0.6%, Mn: 0.1-0.5%, Cu: 0.9-3.5%, Ni: 3.0-6.0%, Cr: 16.5-19%, Mo: 1-4%, N: 0.01-0.2%, and further contains P: 0.02% or less, S: 0.002% or less, Al: 0-1%, V: 0-0.6%, Nb: 0-0.5%, W: 0-3.50%, Co: 0-1.5%, with the balance being Fe and unavoidable impurities. Each component will be described below. Note that % indicating the content of each component means % by mass unless otherwise specified.

[0020] C: 0.002 to 0.05% C is an element that increases the strength of stainless steel. In the present invention, the desired strength can be achieved by including 0.002% or more of C. On the other hand, if the C content exceeds 0.05%, the toughness decreases. Therefore, the C content is set to 0.002 to 0.05%. The C content is preferably 0.005 to 0.04%, and more preferably 0.015 to 0.035%.

[0021] Silicon: 0.05 to 0.6% Silicon acts as a deoxidizer. The effect as a deoxidizer is obtained when the silicon content is 0.05% or more. On the other hand, if the Si content exceeds 0.6%, the hot workability decreases. Therefore, the Si content is set to 0.05 to 0.6%, preferably 0.09 to 0.5%, and more preferably 0.2 to 0.4%.

[0022] Mn: 0.1-0.5% Mn is an element that increases the strength of martensitic stainless steel, and this effect can be obtained at a content of 0.1% or more. On the other hand, if the Mn content exceeds 0.5%, the toughness decreases. Therefore, the Mn content is set to 0.1 to 0.5%, preferably 0.1 to 0.4%, and more preferably 0.2 to 0.35%.

[0023] Cu: 0.9-3.5% Cu is an element that strengthens the protective film, inhibits hydrogen penetration into the steel, and enhances resistance to sulfide stress cracking and sulfide stress corrosion cracking. This effect can be obtained with a Cu content of 0.9% or more. On the other hand, if the Cu content exceeds 3.5%, it causes grain boundary precipitation of CuS, which deteriorates hot workability. Therefore, the Cu content is set to 0.9 to 3.5%, preferably 1.2 to 3.0%, and more preferably 1.5 to 2.8%.

[0024] Ni: 3.0~6.0% Ni is an element that strengthens the protective film and contributes to improving corrosion resistance. It also increases the strength of steel through solid solution strengthening. This effect becomes significant when the Ni content is 3.0% or more. On the other hand, if the Ni content exceeds 6.0%, the stability of the martensite phase decreases, resulting in a decrease in strength. Therefore, the Ni content is set to 3.0 to 6.0%, preferably 3.0 to 5.5%, and more preferably 3.5 to 4.5%.

[0025] Cr: 16.5~19% Cr is an element that forms a protective film on the surface of steel pipes and contributes to improving corrosion resistance. This effect becomes significant when the Cr content is 16.5% or more. On the other hand, if the Cr content exceeds 19%, the ferrite fraction becomes too high and the desired strength may not be ensured. Therefore, the Cr content is set to 16.5 to 19%. The Cr content is preferably 16.8 to 18.0%. The Cr content is more preferably 17.0 to 17.5%.

[0026] Mo: 1-4% Mo is an element that stabilizes the protective film, thereby increasing resistance to pitting corrosion and enhancing resistance to sulfide stress cracking and sulfide stress corrosion cracking. To obtain these effects, a Mo content of 1% or more is required. On the other hand, since Mo is an expensive element, a Mo content of more than 4% leads to an increase in material costs and a decrease in toughness and resistance to sulfide stress corrosion cracking. Therefore, the Mo content is set to 1 to 4%. The Mo content is preferably 1.5 to 3.5%, and more preferably 2.0 to 3.0%.

[0027] N: 0.01 to 0.2% N is an inexpensive element that suppresses the formation of δ-ferrite and improves hot workability. This effect can be obtained with an N content of 0.01% or more. On the other hand, if the N content exceeds 0.2%, nitrides are formed and the toughness is reduced. Therefore, the N content is set to 0.01 to 0.2%. The N content is preferably 0.02 to 0.15%, and more preferably 0.05 to 0.1%.

[0028] P:0.02% or less P is an element that reduces carbon dioxide corrosion resistance, pitting corrosion resistance, and SSC resistance. It is preferable to reduce the content as much as possible, but an extreme reduction leads to a rise in manufacturing costs. For this reason, the P content is set to 0.02% or less as a range that can be industrially implemented relatively inexpensively without causing an extreme deterioration of properties. The P content is preferably 0% or more and 0.01% or less.

[0029] S: 0.002% or less Since S significantly reduces hot workability, it is preferable to reduce the content as much as possible, but an extreme reduction leads to a rise in manufacturing costs. For this reason, the S content is set to 0.002% or less as a range that can be implemented industrially at relatively low cost without causing an extreme deterioration of properties. The S content is preferably 0% or more and 0.001% or less.

[0030] Al: 0-1% The Al content may be 0%, but since Al is an element that acts as an oxygen scavenger, the Al content may be 0.001% or more in order to obtain this effect. On the other hand, if the Al content exceeds 1%, the amount of oxide increases and the toughness deteriorates. Therefore, the Al content is set to 1% or less. The Al content is preferably 0.015 to 0.8%, and more preferably 0.025 to 0.7%.

[0031] V: 0 to 0.6% The V content may be 0%, but since V is an element that improves the strength of seamless steel pipes by precipitation strengthening, the V content may be 0.01% or more to obtain this effect. On the other hand, if the V content exceeds 0.6%, the toughness decreases, so the V content is set to 0.6% or less. The V content is preferably 0.03 to 0.5%, and more preferably 0.07 to 0.45%.

[0032] Nb: 0-0.5% The Nb content may be 0%, but since Nb is an element that improves the yield strength by precipitating as Nb carbide, the Nb content may be 0.01% or more in order to obtain this effect. On the other hand, if the Nb content exceeds 0.5%, it leads to a decrease in toughness and resistance to sulfide stress cracking. Therefore, the Nb content is set to 0.5% or less. The Nb content is preferably 0.07 to 0.4%, and more preferably 0.1 to 0.3%.

[0033] W: 0~3.50% The W content may be 0%, but since W is an element that improves strength, the W content may be 0.01% or more in order to obtain this effect. On the other hand, if the W content is more than 3.50%, the toughness deteriorates. Therefore, the W content is set to 3.50% or less. The W content is preferably 0.05 to 0.3%, and more preferably 0.07 to 0.2%.

[0034] Cobalt: 0-1.5% The Co content may be 0%, but since Co is an element that improves SSC resistance, the Co content may be 0.01% or more to obtain this effect. On the other hand, if the Co content exceeds 1.5%, the hot workability decreases. Therefore, the Co content is set to 0.01 to 1.5% or less. The Co content is preferably 0.03 to 0.15%, and more preferably 0.05 to 0.1%.

[0035] The remainder of the composition other than the above is Fe and unavoidable impurities. Examples of the unavoidable impurities in the remainder include Sn, As, and Sb. However, as long as the effects of the present invention are not impaired, Sn, As, and Sb may each be contained in an amount of 0.1% or less.

[0036] The seamless steel pipe of the present invention is not particularly limited, but the pipe thickness (wall thickness) is preferably 15 mm or more, and more preferably 25 mm or more. Also, the seamless steel pipe of the present invention is not particularly limited, but the pipe thickness (wall thickness) is preferably 45 mm or less, and more preferably 40 mm or less.

[0037] The seamless steel pipe of the present invention may be a stainless steel seamless steel pipe. Also, the seamless steel pipe of the present invention may be a stainless steel seamless steel pipe for oil wells.

[0038] [Method of manufacturing seamless steel pipes and method of drilling holes in rolled material] Fig. 2 is a schematic diagram showing the Mannesmann mandrel mill process, which is one of the methods for producing a seamless steel pipe. An example of the method for producing a seamless steel pipe of the present invention will be mainly described with reference to Fig. 2.

[0039] First, as shown in FIG. 2 (1), in the first step of the manufacturing method of seamless steel pipes, a rolled material (round steel billet) 1 having the above-mentioned composition is heated in a rotary heating furnace 11. Next, as shown in (2), in the second step, the rolled material (round steel billet) 1 heated in the rotary heating furnace 11 is pierced and rolled by a piercer (PCM) 13 to obtain a mother pipe 3. Next, as shown in (3), in the third step, the mother pipe 3 is elongated and rolled by a mandrel mill (MDM) 15. This reduces the wall thickness of the mother pipe 3. Next, as shown in (4), in the fourth step, the mother pipe 3 reduced in wall thickness by the mandrel mill 15 is heated again in a reheating furnace (WBF) 17. Next, as shown in (5), in the fifth step, the mother pipe 3 heated in the reheating furnace 17 is sizing-rolled to a predetermined wall thickness and outer diameter by a hot stretch reducer (HSR) 19.

[0040] Circumferential shear strain imparted to the center of the thickness of the rolled material by piercing rolling: 0.48 or more Here, the reason for specifying the circumferential shear strain generated during piercing and rolling as shown in (2) in Fig. 2 will be explained. In the present invention, the circumferential shear strain imparted to the center of the wall thickness of the rolled material by piercing and rolling must be 0.48 or more. If the circumferential shear strain is less than 0.48, the ferrite grain size becomes coarse, and at least one of the strength and toughness cannot be achieved to a desired value. Although there is no particular upper limit, from the viewpoint of the outer surface quality of the seamless steel pipe, the circumferential shear strain is preferably 1.40 or less. That is, the circumferential shear strain is preferably 0.48 or more and 1.40 or less. The circumferential shear strain is more preferably 0.48 or more and 1.30 or less, even more preferably 0.48 or more and 1.10 or less, and even more preferably 0.48 or more and 0.59 or less.

[0041] In the present invention, even when the area reduction rate is low, it is possible to obtain excellent mechanical properties, and the present invention may be applicable to product sizes with an area reduction rate of 50% or less. Here, the area reduction rate is expressed by the following formula (1) relating to the circumferential cross-sectional area of ​​the round billet (the area of ​​a cross section of the round billet perpendicular to the tube axis direction) and the circumferential cross-sectional area of ​​the piercing-rolled mother tube (the area of ​​a cross section of the mother tube perpendicular to the tube axis direction). Reduction rate (%) = 100 × (circumferential cross-sectional area of ​​round billet (mm 2 )-Circumferential cross-sectional area of ​​the blank pipe after piercing and rolling (mm 2 )) / Circumferential cross-sectional area of ​​round billet (mm 2 ) · · · (1)

[0042] The shear strain in the circumferential direction imparted to the central portion of the thickness of the rolled material can be calculated by the finite element method after piercing and rolling.

[0043] The seamless steel pipe of the present invention is manufactured by using the above-mentioned piercing-rolling of a seamless steel pipe. In the manufacturing method of the seamless steel pipe of the present invention, the conditions in the piercing-rolling are not particularly limited except for the circumferential shear strain imparted to the central part of the wall thickness of the rolled material, but for example, the quenching conditions of the mother pipe obtained by piercing-rolling may be a quenching temperature of 900 to 1150°C and a quenching time of 20 to 80 minutes, and the subsequent tempering conditions may be a tempering temperature of 450 to 700°C and a tempering time of 30 to 90 minutes. EXAMPLES

[0044] The present invention will be described in detail below with reference to the following examples. The present invention is not limited to the following examples, and may be modified as appropriate within the scope of the present invention, and all such modifications are included in the technical scope of the present invention. A round steel billet with an outer diameter of 58 mm and a length of 250 mm was produced from the starting material obtained by preparing molten steel having the chemical composition shown in Table 1. In the second process shown in FIG. 2 (2), the blank tube produced under the piercing-rolling conditions shown in Table 1 was subjected to heat treatment under the conditions of quenching: 960°C x 30 minutes (water cooling) and tempering: 615°C x 70 minutes (air cooling) to obtain a seamless steel tube.

[0045] To measure the structure of the obtained seamless steel pipe, a test piece for microstructural observation was first taken from the center of the wall thickness (at t / 2 position (t: wall thickness)) of a cross section (circumferential cross section of the bare pipe) perpendicular to the pipe axis direction of the seamless steel pipe. The taken sample (test piece for microstructural observation) was corroded with Villela's reagent (a mixture of picric acid, hydrochloric acid, and ethanol in the proportions of 2 g, 10 ml, and 100 ml, respectively), and the structure in the center of the wall thickness was photographed with a scanning electron microscope (magnification: 1000 times), and the structure fraction (volume %) of the ferrite phase was calculated using an image analyzer. The test pieces for X-ray diffraction were ground and polished so that the cross section perpendicular to the tube axis direction (circumferential cross section of the bare tube) became the measurement surface, and the amount of retained austenite (γ) was measured using X-ray diffraction. The amount of retained austenite was calculated by measuring the integrated intensity of the diffracted X-rays on the (220) plane of γ and the (211) plane of α, using the following formula: γ(volume ratio)=100 / (1+(IαRγ / IγRα)) (where Iα is the integrated intensity of α, Rα is the theoretically calculated value of α, Iγ is the integrated intensity of γ, and Rγ is the theoretically calculated value of γ) The fraction (volume fraction) of the tempered martensite phase was defined as the remainder other than the ferrite phase and the retained austenite phase determined by the above-mentioned measurement method.

[0046] The measurement region for the average grain size of ferrite in the seamless steel pipe was a region that was 10% of the wall thickness, with the central part of the wall thickness of the seamless steel pipe being the center in the wall thickness direction. The average grain size of ferrite was measured at 100 mm using electron backscatter diffraction (EBSD). 2 The crystal orientation was measured for the continuous region, and the average value (number average value) of ferrite crystals was calculated by defining grains with a crystal orientation difference of 15° or less as the same crystal grain.

[0047] The yield strength was measured by taking API5CT arc tensile test specimens (see (1) in Figure 3) and V-notch test specimens (5 mm thick) (see (2) in Figure 3) from seamless steel pipes. Specifically, for the API5CT arc tensile test, the sampling start position was 50 mm from the rear end of the seamless steel pipe in the rolling direction in the axial direction, and the sampling target area was up to a position 200 mm in the axial direction. In addition, for the V-notch test pieces (5 mm thick), the starting positions for sampling were 100 mm, 155 mm, and 210 mm in the axial direction from the rear end of the seamless steel pipe in the rolling direction, and a total of three test pieces with a length of 55 mm in the axial direction were sampled. Tensile tests were then conducted in accordance with API5CT standards to determine strength. In addition, V-notch test pieces (5 mm thick) were taken from the obtained test piece material in accordance with JIS Z 2242 (2023) standards, with the test piece's longitudinal direction being the tube axis direction, and a Charpy impact test was conducted. The test was conducted at room temperature (25°C) and toughness was evaluated. For the Charpy impact test, the number average toughness value of three test pieces was evaluated as the toughness value.

[0048] [Table 1]

[0049] As can be seen from Table 1, by satisfying the conditions of the present invention, even with a low area reduction rate (50% or less), a seamless steel pipe having excellent strength and toughness due to grain refinement can be manufactured. [Explanation of symbols]

[0050] 1 Round steel billet 3. Plain tube 10 Seamless steel pipe 11 Rotary heating furnace 13 Piercer 15 Mandrel Mill 17 Reheating furnace 19 Hot Stretch Reducer X Test piece for structural observation

Claims

1. In terms of volume ratio, 40% or more of tempered martensite phase; 25% or more and 40% or less of a ferrite phase; A structure consisting of a retained austenite phase of more than 10% and not more than 25%; When crystal grains having a crystal orientation difference of 15° or less are defined as the same crystal grain, the average ferrite grain size is 35 μm or less, The yield strength is 758 MPa or more, A seamless steel pipe having a toughness value of 60 J or more at 25°C.

2. The composition of the ingredients is as follows: In mass percent, C: 0.002-0.05%, Si: 0.05-0.6%, Mn: 0.1 to 0.5%, Cu: 0.9 to 3.5%, Ni: 3.0 to 6.0%, Cr: 16.5-19%, Mo: 1 to 4%, N: 0.01-0.2%, Contains moreover, P: 0.02% or less, S: 0.002% or less, Al: 0 to 1%, V: 0 to 0.6%, Nb: 0 to 0.5%, W: 0-3.50%, Co: 0 to 1.5%; The seamless steel pipe according to claim 1, wherein the balance consists of Fe and unavoidable impurities.

3. A method for piercing a rolled material when producing the seamless steel pipe according to claim 1 or 2, A method for piercing a rolled material, in which a circumferential shear strain imparted to a central portion of the thickness of the rolled material by piercing-rolling satisfies 0.48 or more.

4. A method for producing a seamless steel pipe, comprising the steps of: producing a seamless steel pipe by using the method for piercing a rolled material according to claim 3 .

Citation Information

Patent Citations

  • Inclined rolling method and method for manufacturing seamless steel pipe

    JP2024000976A

  • High-strength seamless stainless steel pipe and method of manufacturing high-strength seamless stainless steel pipe

    US20190100821A1

  • Stainless steel for oil wells and stainless steel pipe for oil wells

    WO2013146046A1

  • High strength seamless stainless steel pipe and manufacturing method therefor

    WO2017010036A1

  • High strength stainless steel seamless pipe for oil well and manufacturing method therefor

    WO2017138050A1